1999
DOI: 10.1002/(sici)1097-0290(19990420)63:2<154::aid-bit4>3.3.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic grafting of a natural product onto chitosan to confer water solubility under basic conditions

Abstract: Chitosan is a natural biopolymer whose rich amine functionality confers water solubility at low pH. At higher pH's (greater than 6.5), the amines are deprotonated and chitosan is insoluble. To attain water solubility under basic conditions we enzymatically grafted the hydrophilic compound chlorogenic acid onto chitosan. Despite its name, chlorogenic acid is a nonchlorinated phenolic natural product that has carboxylic acid and hydroxyl functionality. The enzyme in this study was tyrosinase, which converts a wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(89 citation statements)
references
References 16 publications
4
83
0
2
Order By: Relevance
“…For example, the enzymatic treatment of chitosan in the presence of chlorogenic acid produced the modified chitosan, soluble under both acidic and basic conditions. [57] The PPO catalyzed reaction of chitosan and 3,4-dihydroxyphenylethylamine (dopamine) provided water resistant adhesive properties to chitosan. [58] A chitosan derivative modified with hydroxy or dihydroxybenzaldehyde was crosslinked by PPO to give stable and self-sustaining gels.…”
Section: Biopolymer-flavonoid Conjugatesmentioning
confidence: 49%
“…For example, the enzymatic treatment of chitosan in the presence of chlorogenic acid produced the modified chitosan, soluble under both acidic and basic conditions. [57] The PPO catalyzed reaction of chitosan and 3,4-dihydroxyphenylethylamine (dopamine) provided water resistant adhesive properties to chitosan. [58] A chitosan derivative modified with hydroxy or dihydroxybenzaldehyde was crosslinked by PPO to give stable and self-sustaining gels.…”
Section: Biopolymer-flavonoid Conjugatesmentioning
confidence: 49%
“…A potential environmental benefit for using enzymes is that their selectivity may be exploited to eliminate the need for waste full protection and deprotection steps. Finally, enzymes specificity may offer the potential for precisely modifying macromolecular structure to better control polymer function [45,46]. For instance, enzymatic modification can yield chitosan derivatives with unique pH-sensitive water solubility and adhesive properties.…”
Section: Enzymatic Graftingmentioning
confidence: 99%
“…Kumar et al [45] reported that enzymatic grafting of phenolic compounds onto chitosan confer water solubility under basic conditions (Fig. 3).…”
Section: Enzymatic Graftingmentioning
confidence: 99%
“…In summary, the results in Figures 1 and 2 provide UV-visible evidence for the covalent modification of chitosan by p-cresol and tyrosinase. The differences between chitosan and cellulose and the observed absorption peak at 460 nm for the modified chitosan are consistent with a covalent modification through amino groups of chitosan previously reported (19)(20)(21)(22)(23).…”
Section: Oxidation Of P-cresol To Quinone and Adsorption On A Chitosamentioning
confidence: 99%